Pengaruh Pendampingan Ibu Pekerja Harian Lepas Terhadap Tingkat Stres Akademik Pembelajaran Daring Siswa Sekolah Dasar - Indah Fatmawati; Nurhayati Djamas; Anisa Rahmadani (Faktor Jurnal Ilmiah Kependidikan, 2021)
This research aims to know the effect of daily-paid worker mother’s assistance on the academic stress level of primary school online learning. Using a quantitative approach, the measuring instruments used are Academic Stress Level Scale and Mother Assistance Scale. Test data were analyzed with a simple regression. The research sample was 56 students in grades 5-6 SD in Kasih Ibu La Tansa foundation, South Jakarta, Indonesia. The results showed that the coefficient of determination is -0.647 which indicated that there was a negative effect of daily-paid worker mother’s assistance on the academic stress level of primary school student online learning and the R square number is 0.418 which indicated that the contribution of mother’s assistance had a significant effect of 41.8% on the academic stress level of online learning elementary school students. So that mothers need to accompany their children in online learning. School counselor and homeroom teachers should provide stress management skills in accordance with the developmental stages of elementary school students.